Model reference adaptive system and pseudo-sliding mode control with exponential reaching law for sensorless-speed control of PMSM. - Djaloul Karboua; Toufik Mebkhouta; Said Benkaihoul; Youcef Chouiha; Belgacem Toual; Zuhair A Alqarni; Ahmad F Tazay; Mohamed I Mosaad (PLoS ONE)
Sensorless speed motor drives are essential for developing control techniques, reducing cost, streamlining the system, and enhancing reliability. This study explores the area of sensorless speed control for Permanent Magnet Synchronous Motors (PMSMs) by proposing a hybrid control technique. This technique integrates the model reference adaptive system (MRAS) and pseudo-sliding mode control with an Approach Reaching Law (ARL). The MRAS is implemented as a robust sensorless observation method that efficiently handles uncertainties, adapts to dynamic conditions, and aims to achieve dependable performance by having the controlled system mimic a reference model. On the other hand, the pseudo-sliding mode control entails using a continuous approximation (CA) methodology to successfully resolve the chattering problem often seen in conventional sliding mode control approaches. This approach of control allocation enables more seamless control signals, hence improving the longevity of the system and minimizing unwanted oscillations. The ARL component relies on the Exponential Reaching Law (ERL), which enables fast and precise convergence to the intended sliding surface. The exponential characteristics of the ERL lead to faster reaction times and enhanced dynamic performance, guaranteeing the timely attainment of the sliding surface while being robust against changes in parameters and external disturbances. To assess the efficacy of the proposed sensorless hybrid control approach, uncertainties and disturbances were simulated, including PMSM parameters variation, load torque application, and speed level changes. The effectiveness of the suggested approach is compared to control strategies for PMSM, such as the classical ERL-SMC (Type 1) and the pseudo-sliding mode ERL-SMC (Type 2) schemes. The simulations were conducted exclusively using MATLAB/Simulink.